Retaining knowledge worker through motivation - Hway, Boon Ong; Lee, Lee Chong; Mohd Hatta, Kasuma Nurhazwani (2016)
This study examines how knowledge workers could be retained to meet the demand of the local industry. A survey was carried in Iskandar Malaysia to gauge the knowledge workforce’s views on what motivated them to continue working in Malaysia. A seven Likert-scale questionnaire was distributed to workers that had at least a first degree or higher diploma education from a local or foreign institution of higher education.Out of the 200 questionnaires distributed to employees of randomly selected companies identified in the ICT Blueprint for 2020 Iskandar Malaysia, 145 was complete and usable for analysis.Data collected were analysed using reliability test, factor analysis and multiple regression.